Metal Distribution and Characterization of Cultivable Lead-Resistant Bacteria in Shooting Range Soils. Issue 4 (18th May 2016) - Adler, Aline; Devarajan, Naresh; Wildi, Walter; Poté, John
ABSTRACT: Shooting ranges represent about 10% of polluted sites in Switzerland. This pollution, mainly consisting of lead (Pb) and antimony (Sb), can spread into the local groundwater, wildlife and plants. In this study, shooting range stop butt soils (elevated soil mount behind the target) of three sites (Versoix, Cartigny and Nyon, Western Switzerland) were investigated for metal contamination and culturable lead-resistant bacteria in contaminated soils. The inductively coupled plasma mass spectrometry analysis of surface stop butt soils (0–5 cm) indicated high metal concentrations especially for Pb and Sb, e.g., the Pb concentration ranging from 61, 135 to 395, 651, 23, 821 to 201, 268 and 120 to 27, 517 mg kg −1 in the soil from the sites of Versoix, Cartigny and Nyon, respectively. Molecular analysis of 16S rRNA gene demonstrates the presence of bacteria from diverse classes: Flavobacteriia, α-Proteobacteria, γ-Proteobacteria, Actinobacteria and Bacilli that exhibited high Pb minimum inhibitory concentration value from 1, 036 to 2, 694 mg kg −1 . The isolated strains could be the subject of further studies to evaluate their role in bioremediation of lead-contaminated soil.